Peran Perempuan Muhammadiyah Dalam Kepemimpinan Dan Politik Di Kalimantan Tengah - Indah Tri Handayani; Srie Rosmilawati; Mambang Mambang (Pencerah Publik, 2019)
In the present condition, the movement of ' Aisyiyah and Nayiatul Aiyiyah women is still needed and developed in particular in central Kalimantan, by looking at the current challenges and socio-political conditions. In the context of Muhammadiyah, the strengthening of women's movements in the requirement is inherent with the mission and dynamics of the Muhammadiyah movement in realizing the true Islamic community. The revitalization of Muslim women's movements is also in line with Islamic missions as a religion that upholds the glory of women and humanity to become the world's majesty and as a treatise on the pamphlets of the secret of Lil'alamin. Thus, researchers are interested in reviewing the role of Muhammadiyah women in leadership and political affairs. Research objects that serve as the subject of research have complex and dynamic characteristics. Based on the results of the study of about 70% of Muhammadiyah women both Aisyiyah and Nasyiatul Aisyiyah have been actively involved in leadership and political roles in Central Kalimantan. The activities are directly involved in the government agency and the political, KPU, etc. and can also be done orally through studies, meetings held or personally. The quota of 30 percent of women in Parliament and political parties was not wasted by the district leader ' Aisyiyah to issue a policy on women's political Empowerment program, giving women a political education. The Program is listed in activities including seminars, workshops, studies, studies, training and so on, in providing support to women to participate in the political field in central Kalimantan. The department owned by the Women of Muhammadiyah both Aisyiyah and Nasyiatul Aisyiyah in addition to the obligation in the domestic domain is a classic problem that serves as a test of commitment in the air-conditioned ma'ruf nahi munkar.